PERANAN INTERNAL AUDIT TERHADAP PENGENDALIAN PIUTANG USAHA PADA CV. EKATUNGGAL CABANG SIDOARJO - Aisyah Puspita Sari; Hendra Dwi Prasetya; Wardhani, Parwita Setya (Ekomania, 2023)
Receivables are an important part of the company's assets, in smoothing the distribution of company income, then used as a prolonged turnover of company assets. In improving accounts receivable control, a mature internal audit system is needed. Internal audit is a series of activities that are expected to assist management in reviewing operating procedures and taking into account the level of effectiveness of each business unit through the internal control system. In the development of internal control of accounts receivable, it is strongly influenced by the role of internal audit because not a few of the billing system that does not reach the company has the potential to cause fraud from the company's internal parties. The role of an adequate internal audit and an auditor who is competent in the analysis of accounts receivable reports, can facilitate the purpose of planning and controlling these receivables by minimizing the potential for fraud and minimizing losses that arise due to uncollectible receivables. This research was conducted with the aim of knowing the role of internal audit in controlling accounts receivable at CV. EKATUNGGAL Sidoarjo Branch. The author uses a descriptive research method, where the descriptive method has the aim of formulating, presenting, and analyzing data that clearly describes the object of research and draws appropriate conclusions based on the research conducted. The data obtained by the next author will be processed and analyzed with reference to the theories that have been studied. The author concludes and formulates based on the results of research and discussion, that the role of internal audit in CV. EKATUNGGAL is adequate so that it can support and increase effectiveness in internal control of accounts receivable.